The Lettered University. University Teaching and Research in Spain - Martínez Chicón, Raquel; Olmos Alcaraz, Antonia (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
The present paper performs a metaphorical comparison between the Lettered city described by Ángel Rama and the reality of the Spanish University today with the same claim: «the democratization of intellectual functions». For this we will resort to an auto-ethnographic methodology, and the narration of ours experiences inside the Academy. We focus on the increased mercantilization of the institution and «new Lettereds» —agencies of control of knowledge and quality— and reflected on some social categories such as age and gender as builders of difference and maintainer of structures of power and inequality.
Keywords: democracy and ethics at the University; mercantilization of knowledge; identity; power relations; The Lettered City